Data security and protection techniques in big data:a survey - Kai-min WEI; Jian WENG; Kui REN (网络与信息安全学报)
Big Data has attracted tremendous attention from all over the world nowadays.Its sheer volume,complex structure and realtime processing requirements often obsolete traditional technologies when coming to provide suffi-cient security protection.To address this challenge,significant research efforts have been carried out by the research community since recent years.Different technical aspects of big data security,including encryption algorithms,data integrity auditing,access control,secure data duplication,assured deletion,and secure search were surveyed,and in-depth discussions on their pros and cons were provided.Various future research directions were also discussed.